Identification of TRAF6, a Novel Tumor Necrosis Factor Receptor-associated Factor Protein That Mediates Signaling from an Amino-terminal Domain of the CD40 Cytoplasmic Region - Ishida, Takaomi; Mizushima, Sei-ichi; Azuma, Sakura; Kobayashi, Norihiko; Tojo, Tadashi; Suzuki, Kimie; Aizawa, Shigemi; Watanabe, Toshiki; Mosialos, George; Kieff, Elliott; Yamamoto, Tadashi; Inoue, Jun-ichiro (The Journal of biological chemistry, 1996)
CD40 signalings play crucial roles in B-cell function. To identify molecules which transduce CD40 signalings, we have utilized the yeast two-hybrid system to clone cDNAs encoding proteins that bind the cytoplasmic tail of CD40. A cDNA encoding a putative signal transducer, designated TRAF6, has been molecularly cloned. TRAF6 has a tumor necrosis factor receptor (TNFR)-associated factor (TRAF) domain in its carboxyl terminus and has a RING finger domain, a cluster of zinc fingers and a coiled-coil domain, which are also present in other TRAF family proteins. TRAF6 does not associate with the cytoplasmic tails of TNFR2, CD30, lymphotoxin-Î² receptor, and LMP1 of Epstein-Barr virus. Deletion analysis showed that residues 246-269 of CD40 which are required for its association with TRAF2, TRAF3, and TRAF5 are dispensable for its interaction with TRAF6, whereas residues 230-245 were required. Overexpression of TRAF6 activates transcription factor NFÎºB, and its TRAF-C domain suppresses NFÎºB activation triggered by CD40 lacking residues 246-277. These results suggest that TRAF6 could mediate the CD40 signal that is transduced by the amino-terminal domain (230-245) of the CD40 cytoplasmic region and appears to be independent of other known TRAF family proteins.